Microbial Pre-treatment of Lignocellulosic Biomass for Biofuel Production: A Review - Rana Chhetri, Bibek; Acharya, Dipika; Gautam, Arjun; Bajracharya, Nasala; Shrestha, Anuj; Khadka, Smriti (International Journal of Applied Sciences and Biotechnology, 2022)
Lignocellulosic biomasses (LCB), second-generation biofuels are used as an alternative means to cope with the burning issues of depleting fossil fuels like petroleum products with the added advantage of renewability, lower emission, and lesser pollution. For the increment in the production of LCB biofuels, microbial pre-treatment processes are conducted which accelerates the degradation of organic polymers like lignin and hemicellulose with the activity of potential microorganisms. To increase the efficiency of degradation of hemicellulose, hemicellulolytic fungi including Trichoderma and Aspergillus and other bacteria produce multi-enzymatic complexes like cellulosomes. Similarly, organisms like Tinea versicolor, Dichomitus squalens, Phlebia floridensis, Daedalea flavida, and Phlebia radiata contain lignin-degrading auxiliary enzymes and lignin modifying enzymes like laccase and heme-containing peroxidase which aid in delignification process. Several factors are associated with pre-treatment processes like the type of strain, inoculum load, pH, temperature, fatty acids, C/N ratio, time, aeration, grindability, surface area, particle size, and supplements added. To enhance the pretreatment method, the combination of microbial with physical, chemical, and mechanical methods is suggested which leads to a synergistic effect and better yield of the final product. Overall, biofuels should be more employed and this review aims to bring light to the microbial pre-treatment approaches which can aid in the efficient production of biofuels that can directly contribute to environmental sustainability.